2022
DOI: 10.3390/pharmaceutics14020368
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid as a Non-Selective Inhibitor of α/β-Hydrolase Fold Enzymes Involved in the Inflammatory Process: The Two Sides of the Same Coin

Abstract: (1) Background: Gallic acid (GA) has been characterized as an effective anti-inflammatory, antivenom, and promising drug for therapeutic use. (2/3) Methods and Results: GA was identified from ethanolic extract of fresh pitanga (Eugenia uniflora) leaves, which was identified using commercial GA. Commercial GA neutralized the enzymatic activity of secretory PLA2 (sPLA2) by inhibiting the active site and inducing changes in the secondary structure of the enzyme. Pharmacological edema assays showed that GA strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…This anti-inflammatory effect may also be associated with the presence of gallic acid in both AELR and HELR extracts. It is noteworthy that our results with both L. rigida extracts are corroborated by other reports, indicating that gallic acid is a subject of study due to its beneficial therapeutic activities, such as its role in the regulation of extracellular platelet-activating factor and modulation of the inflammatory process [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…This anti-inflammatory effect may also be associated with the presence of gallic acid in both AELR and HELR extracts. It is noteworthy that our results with both L. rigida extracts are corroborated by other reports, indicating that gallic acid is a subject of study due to its beneficial therapeutic activities, such as its role in the regulation of extracellular platelet-activating factor and modulation of the inflammatory process [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…GA and MG, which are secondary metabolites of plants generally found in many foods and beverages, have gained attention due to their favorable safety information [11,12]. GA and MG have been reported to offer many health benefits, including antioxidant [13], anti-cancers [14,15], anti-inflammatory [16,17] and antimicrobial effects [18][19][20]. Their pharmacological activities have been documented to be associated with enzyme inhibition because of the protein-binding capabilities of phenolic compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sharanya et al (2018) showed that MG could inhibit lipoxygenase activity through wetlaboratory experiments and in silico studies, highlighting its potential anti-inflammatory therapy [16]. Similarly, GA shows promise in inflammatory therapy due to its inhibitory effect on phospholipase A2 [17]. However, the inhibition of bacterial enzymes or virulence by other phenolic compounds have been reported to be either associated or not associated with their antibacterial activity [22].…”
Section: Introductionmentioning
confidence: 99%
“…GA bio efficacy impact has been the subject of many research papers and reviews to date. GA has many biological properties 1 which includes antioxidant [2][3] , anticancer property [4][5] , anti-inflammatory 6 , antidiabetic [7][8] , anti-ulcerogenic 9 . GA is also safe against disorders like radical oxygen species (ROS), hyper production, oxidative stress (OS) 10 and bacterial infections 11 .…”
Section: Introductionmentioning
confidence: 99%